Use of library resources and Services in Nigerian agricultural research institutes: The case of two research libraries in Ibadan, Oyo State (2012)
This study was carried out to assess the extent to which agricultural researchers make use of the research - based collections and Services in agricultural research libraries in Ibadan, Oyo State. It adopted the descriptive survey research design. Two hundred library users from two agricultural research institutes in Ibadan were selected as participants using simple random sampling technique. Questionnaire was used as an instrument to collect data which were analysed using descriptive statistics of frequencies counts and percentages. Results showed that the library resources and Services were not very adequate to attract high level of patronage by the agricultural researchers. Study also revealed that access to the available resources was impaired by a number of factors. Recommendations are therefore made to further promote the use of library resources and Services. Most importantly, it was recommended that current research-based collection, both in print and electronic formats, should be developed in a digital environment.